IDENTIFIKASI, DESKRIPSI FAKTOR DAN DAMPAK PENGGUNAAN MAJAS DALAM ONLINE SHOP PLATFORM SHOPEE - Arifah, Cindy Nur; Sabardilla, Atiqa (Universitas Wiralodra, 2022)
Along with the times, language has become one of the things that cannot be separated from the influence of the internet. One of them is the use of figure of speech in online shop. Research on figurative language has often been researched. However, figurative research on the Shopee platform has not been researched. Data collection was carried out through the listening method accompanied by an advanced note-taking technique. This research was processed using a qualitative descriptive method. The results showed that the use of figure of speech in the shopee online shop platform consisted of 4 forms, namely metaphorical figure of speech (13%), personification (61%), hyperbole (23%), and allusion (13%) of the 15 data analyzed. The tendency to use figure of speech in advertisements on the shopee platform is carried out to increase the effectiveness of communication in buying and selling and to beautify diction so that consumers are interested in the products offered. The impact of using figure of speech in advertising on the shopee platform is that it can give rise to a different perspective with an exaggerated impression.